Therapeutic Role of Inducible Nitric Oxide Synthase Expressing Myeloid-Derived Suppressor Cells in Acetaminophen-Induced Murine Liver Failure - Hsu, Chen-Yu; Lin, Yung-Chang; Chang, Li-Yuan; Huang, Sheng-Kai; Huang, Chien-Hao; Yang, Chan-Keng; Huang, Ching-Tai; Lin, Chun-Yen (Frontiers in Immunology, 2020)
Background Acetaminophen (APAP) overdose is one of the major etiologies of liver failure. Hepatocyte necrosis induced by toxic metabolites of APAP can activate proinflammatory responses, including elastase-expressing neutrophils, to exacerbate liver injury. Myeloid-derived suppressor cells (MDSCs) increased in inflammation can inhibit proinflammatory responses. Our aim is to investigate the role of MDSC in APAP-induced liver failure and the possible therapeutic application. Methods BLAB/c mice were injected with a sublethal/lethal dose of APAP as the murine model of liver failure. MDSCs were defined as CD11b+Gr-1+ cells with the ability of T-cell suppression. Results A sublethal challenge of APAP could increase the intrahepatic MDSC and protect mice against subsequent lethal challenge of APAP, lipopolysaccharide (LPS)/D-galatosamine or concanavalin A. This protection was lost if MDSCs were depleted and inducible nitric oxide synthase (iNOS) was the key molecule in this MDSC-mediated protection. Taking advantage of these observations, different bone marrow-derived MDSCs (BM-MDSCs) were generated. Among different cytokine-treated BM-MDSCs, tumor necrosis factor alpha/LPS-primed MDSCs (TNF-α/LPS MDSCs) had the strongest liver-protection ability after adoptive transfer. Further mechanistic explorations showed, iNOS-expressing TNF-α/LPS MDSCs induced the apoptosis of activated neutrophil and decreased the intrahepatic infiltration of elastase-expressing neutrophil. Moreover, we generated MDSCs from human peripheral blood mononuclear cells (PBMCs) with similar phenotype. Conclusion We demonstrated the protective role of MDSCs and therapeutic effect of TNF-α/LPS MDSCs in APAP-induced liver failure. MDSC might protect against the APAP-induced liver failure by reducing the intrahepatic infiltration of activated neutrophil to limit inflammation. Therefore, a therapeutic role of MDSCs for APAP-induced liver failure was proposed.